2020
DOI: 10.1099/mgen.0.000456
|View full text |Cite
|
Sign up to set email alerts
|

Whole-genome epidemiology links phage-mediated acquisition of a virulence gene to the clonal expansion of a pandemic Salmonella enterica serovar Typhimurium clone

Abstract: Epidemic and pandemic clones of bacterial pathogens with distinct characteristics continually emerge, replacing those previously dominant through mechanisms that remain poorly characterized. Here, whole-genome-sequencing-powered epidemiology linked horizontal transfer of a virulence gene, sopE, to the emergence and clonal expansion of a new epidemic Salmonella enterica serovar Typhimurium (S. Typhimurium) clone. The sopE ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 70 publications
(164 reference statements)
0
32
0
Order By: Relevance
“…However, a Bayesian analysis focusing only on genomes with this gene could confirm the chronological sequence of events identified. Three identical copies of sopE were recently identified in the genome of the monophasic S. Typhimurium ST34 strain S01569-10 ( Tassinari et al, 2020). Two chromosomal copies of sopE gene were located in distinct prophages, designated mTmV1569 and m1569, and the third copy of the sopE gene was present in strain S01569-10 on an 81.1 Kb prophage plasmid, designated pS01569 (Tassinari et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a Bayesian analysis focusing only on genomes with this gene could confirm the chronological sequence of events identified. Three identical copies of sopE were recently identified in the genome of the monophasic S. Typhimurium ST34 strain S01569-10 ( Tassinari et al, 2020). Two chromosomal copies of sopE gene were located in distinct prophages, designated mTmV1569 and m1569, and the third copy of the sopE gene was present in strain S01569-10 on an 81.1 Kb prophage plasmid, designated pS01569 (Tassinari et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The temperate prophages mTmV and mTmV2, carrying virulence sopE gene described in S. 1,4,[5],12:i:-ST34 (Petrovska et al, 2016;Tassinari et al, 2020) was also shown to lead to a clonal expansion of this clone in the UK (Tassinari et al, 2020).…”
Section: 4[5]12:i:-st34 Isolatesmentioning
confidence: 99%
“…1 ,4,[5],12:i:-) ST34 rapidly emerging in pig populations around the world. 8 , 15 , 16 U288 and ST34 co-existed in the UK pig population and together accounted for around 80% of isolates. 17 Despite, approximately half of all pork consumed in the UK being from UK pig herds, 18 since its emergence U288 have rarely been isolated from human infections in the UK.…”
Section: Introductionmentioning
confidence: 99%
“…For example, an outbreak of enteroaggregative hemorrhagic E. coli O104:H4 that led to 3,842 human infections was reported to have gained virulence through the uptake of a Stx2a virulence marker by way of a Shiga toxin-encoding bacteriophage [146]. More recently, whole-genome sequencing-based epidemiological analysis has indicated the horizontal transfer of the sopE virulence gene via temperate bacteriophage mTmV, leading to the emergence and clonal distribution of a new epidemic S. enterica Typhimurium clone [147]. The second scenario involves certain pathogenic bacteria which harbor a multitude of prophages, with each phage-encoded virulence factor contributing a small amount to the overall pathogenicity of the lysogen [92].…”
Section: Additional Contributions Of Bacteriphages To Bacterial Virulmentioning
confidence: 99%